MEDICAL TOURISM: CURRENT STATE AND PROSPECTS OF DEVELOPMENT IN UKRAINE - MOSKVYAK, Yaroslava (Herald of Khmelnytskyi National University. Economic sciences, 2022)
Current trends in tourism are the separation from classical tourism of the latest, diverse types and forms, which can enrich the income from tourism services and create prospects for entering new markets, including international ones. The growth of the market of tourist services is due to the growth of both demand and supply. The increase in supply is mainly due to the development of entrepreneurship, caused by high levels of turnover and profitability capital, competitive potential. Among the new forms and types of tourism that increase the socio-economic potential of the state, medical tourism stands out, the main purpose of which is to organize the treatment of citizens abroad. The field of medical tourism is an important part of the service sector, which plays a significant role in enhancing the country’s trade balance. From a macroeconomic point of view, this is due to a number of factors, such as: demographic, globalization factors, technological change. The aim is to reveal the current state, organizational aspects of the functioning of medical tourism, as a promising area of tourism enterprises in Ukraine. In accordance with the set goal, the tasks were formulated, which determined the logical structure and sequence of their solution: - to reveal the essence and modern approaches to the classification of medical tourism; - describe the organizational and managerial aspects of medical tourism in Ukraine; - to highlight the socio-economic essence of medical tourism; - to analyze the current state and trends in the development of medical tourism in Ukraine and the world; - to reveal the organizational aspects of the medical tourism product and its effectiveness for tourism enterprises; - identify problems and outline prospects for the development of medical tourism in Ukraine. The object of the study is the patterns, quantitative and qualitative indicators of the functioning of medical tourism in Ukraine and the world. The subject of the study is the organizational aspects of medical tourism and medical tourism product to improve the efficiency of tourism enterprises.